Validation of a Unilateral Cleft Lip Surgical Outcomes Evaluation Scale for Surgeons and Laypersons. Issue 9 (September 2017) - Campbell, Alex; Restrepo, Carolina; Deshpande, Gaurav; Tredway, Caroline; Bernstein, Sarah M.; Patzer, Rachel; Wendby, Lisa; Schonmeyr, Bjorn
Abstract : Background: A standardized evaluation tool is needed for the assessment of surgical outcomes in cleft lip surgery. Current scales for evaluating unilateral cleft lip/nose (UCL/N) aesthetic outcomes are limited in their reliability, ease of use, and application. The Unilateral Cleft Lip Surgical Outcomes Evaluation (UCL SOE) scale measures symmetry of 4 components and sums these for a total score. The purpose of this study was to validate the SOE as a reliable tool for use by both surgeons and laypersons. Methods: Twenty participants (9 surgeons and 12 laypeople) used the SOE to evaluate 25 sets of randomly selected presurgical and postsurgical standardized photographs of UCL/N patients. Interrater reliability for surgeon and laypeople was determined using an intraclass correlation coefficient (ICC). Results: Individual surgeons and laypeople both reached an ICC in the "fair to good" range (ICC = 0.42 and 0.59, respectively). Averaging 2 evaluators in the surgeon group improved the ICC to 0.58 and in the laypeople group to 0.74, respectively. Averaging 3 evaluators increased the ICC for surgeons to the "good" range (ICC = 0.71) and the ICC for laypeople to the "very good" range (ICC = 0.82). Conclusions: Surgeon and layperson raters can reliably use the SOE to assess the aesthetics results after surgical repair of UCL/N, and improved reliability and reproducibility is achieved by averaging the scores of multiple reviewers. Abstract : Supplemental Digital Content is available in the text.